Ultrafast CO2 sorption in sol-gel lithium zincate: Rapid kinetics and sequential sorption dynamics - R. Achu; Devika Surendran; Prince George; Atly Pauly; A. Peer Mohamed; Balagopal N. Nair; U.S. Hareesh (Chemical Engineering Journal, 2025)

A novel paradigm for observational learning in rats - Ida V. Rautio; Ella Holt Holmberg; Devika Kurup; Benjamin A. Dunn; Jonathan R. Whitlock (Cognitive Neurodynamics, 2024)
The ability to learn by observing the behavior of others is energy efficient and brings high survival value, making it an important learning tool that has been documented in a myriad of species in the animal kingdom. In the laboratory, rodents have proven useful models for studying different forms of observational learning, however, the most robust learning paradigms typically rely on aversive stimuli, like foot shocks, to drive the social acquisition of fear. Non-fear-based tasks have also been used but they rarely succeed in having observer animals perform a new behavior de novo . Consequently, little known regarding the cellular mechanisms supporting non-aversive types of learning, such as visuomotor skill acquisition. To address this we developed a reward-based observational learning paradigm in adult rats, in which observer animals learn to tap lit spheres in a specific sequence by watching skilled demonstrators, with successful trials leading to rewarding intracranial stimulation in both observers and performers. Following three days of observation and a 24-hour delay, observer animals outperformed control animals on several metrics of task performance and efficiency, with a subset of observers demonstrating correct performance immediately when tested. This paradigm thus introduces a novel tool to investigate the neural circuits supporting observational learning and memory for visuomotor behavior, a phenomenon about which little is understood, particularly in rodents.

The Luna structure, India: A probable impact crater formed by an iron bolide - K.S. Sajinkumar; S. James; G.K. Indu; Saranya R. Chandran; Devika Padmakumar; J. Aswathi; S. Keerthy; M.N. Praveen; N. Sorcar; J.K. Tomson; Anil Chavan; Subhash Bhandari; et al. (Planetary and Space Science, 2024)

The burden of prostate cancer in Trinidad and Tobago: one of the highest mortality rates in the world - Wayne A. Warner; Tammy Y. Lee; Fang Fang; Adana A. M. Llanos; Smriti Bajracharya; Vasavi Sundaram; Kimberly Badal; Vandana Devika Sookdeo; Veronica Roach; Marjorie Lamont-Greene; Camille Ragin; Simeon Slovacek; et al. (Cancer Causes & Control, 2018)